Is Attention Really Effort? Revisiting Daniel Kahneman’s Influential 1973 Book Attention and Effort - Bruya, Brian; Tang, Yi-Yuan (Frontiers in Psychology, 2018)
Daniel Kahneman was not the first to suggest that attention and effort are closely associated, but his 1973 book Attention and Effort, which claimed that attention can be identified with effort, cemented the association as a research paradigm in the cognitive sciences. Since then, the paradigm has rarely been questioned and appears to have set the research agenda so that it is self-reinforcing. In this article, we retrace Kahneman's argument to understand its strengths and weaknesses. The central notion of effort is not clearly defined in the book, so we proceed by constructing the most secure inferences we can from Kahneman's argument regarding effort: it is cognitive, objective, metabolic expenditure, and it is attention. Continuing, we find from Kahneman's argument that effort-attention must be a special case of sympathetic dominance of the autonomic nervous system that is also an increase in metabolic activity in the brain that has crossed a threshold of magnitude. We then weigh this conception of effort against evidence in Kahneman's book and against more recent evidence, finding that it does not warrant the conclusion that effort can be equated with attention. In support of an alternative perspective, we briefly review diverse studies of behavior, physiology and neuroscience on attention and effort, including meditation and studies of the LC-NE system, where we find evidence for the following: 1) Attention seems to be associated not with the utilization of metabolic resources per se but with the readying of metabolic resources in the form of adaptive gain modulation. This occurs under sympathetic dominance and can be experienced as effortful. 2) Attention can also occur under parasympathetic dominance, in which case it is likely experienced as effortless.